ANALYSIS OF SOCIAL RETURN ON INVESTMENT (SROI) IN CREATING SHARED VALUE (CSV) ACTIVITIES IN THE “SAYURPRENEURSHIP 4.0: DIGITALIZATION STRATEGY FOR VEGETABLE TRADERS” PROGRAM - Rani Ayu Asari; Tri Siwi Agustina (Transpublika Publisher, 2024)
Social Return on Investment (SROI) analysis is an important tool in measuring the social impact of a program or activity by comparing the social value generated against the costs incurred. Creating Shared Value (CSV) activities in the